2023
DOI: 10.1136/jnnp-2022-330757
|View full text |Cite
|
Sign up to set email alerts
|

Low protection from breakthrough SARS-CoV-2 infection and mild disease course in ocrelizumab-treated patients with multiple sclerosis after three mRNA vaccine doses

Abstract: BackgroundOur study investigated the rate of breakthrough SARS-CoV-2 infection and clinical outcomes in a cohort of multiple sclerosis (MS) patients who were treated with the anti-CD20 monoclonal antibody (Ab), ocrelizumab, before first, second and third BNT162b2 mRNA vaccinations. To correlate clinical outcomes with the humoral and cellular response.MethodsThe study was a prospective non-randomised controlled multicentre trial observational study. Participants with a diagnosis of MS who were treated for at le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…However, as no severe form of COVID-19 was observed in our cohort, whether this reinforced vaccination scheme would clinically benefit patients with MS on anti-CD20 to prevent severe COVID-19 could not be assessed. A recent study by Novak et al [27] found that 59% of patients on anti-CD20 developed breakthrough non-severe COVID-19 after three injections of SARS-CoV-2 mRNA vaccine. Another study by van Kempen et al [28] found that patients on anti-CD20 and S1PRM had a higher breakthrough COVID-19 rate compared to patients on other treatments, but most infections were mild.…”
Section: Discussionmentioning
confidence: 99%
“…However, as no severe form of COVID-19 was observed in our cohort, whether this reinforced vaccination scheme would clinically benefit patients with MS on anti-CD20 to prevent severe COVID-19 could not be assessed. A recent study by Novak et al [27] found that 59% of patients on anti-CD20 developed breakthrough non-severe COVID-19 after three injections of SARS-CoV-2 mRNA vaccine. Another study by van Kempen et al [28] found that patients on anti-CD20 and S1PRM had a higher breakthrough COVID-19 rate compared to patients on other treatments, but most infections were mild.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have confirmed a greater risk of a breakthrough infection with lower anti-SARS-CoV-2-specific antibody levels and under certain disease-modifying therapies (DMTs) [ 13 , 14 , 15 , 16 ]. Especially under anti-CD20, the COVID-19 disease course was shown to remain more severe even after initial immunisation [ 15 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have identified seroconversion rates by pwMS on B cell-depleting therapies as ∼50% following three COVID-19 vaccine doses, amongst the lowest of any group, with antibody titres in those who do seroconvert inferior to healthy individuals. 58, 10, 12, 13 As such, it has been difficult to interpret the level of protection afforded these patients, particularly against antibody-escape variants such as omicron BA.5, and for clinicians and policy makers to make informed decisions with respect to booster dosing and existing and emerging prophylactic measures.…”
Section: Introductionmentioning
confidence: 99%
“…Common DMTs include the B cell-depleting anti-CD20 monoclonal antibody, ocrelizumab (Ocrevus), and the anti-α4integrin monoclonal antibody, natalizumab (Tysabri). B cell depleting therapies are associated with increased risk of severe COVID-19 disease [1][2][3][4][5] and impaired humoral immune response to vaccination [6][7][8][9][10] in pwMS and other patient populations. In contrast, natalizumab is nondepleting, and no impairment in vaccine response has been identified for pwMS receiving treatment with natalizumab.…”
Section: Introductionmentioning
confidence: 99%